Pengaruh Digital Content Marketing, Influencer Credibility, dan Interaktivitas Media Sosial terhadap Loyalitas Merek di Kalangan Generasi Z - Abbas, Muchlis; Taufik Thahir; Rahmawati Umar; Syahrul Irwandi; Masyadi (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
This study investigates the influence of Digital Content Marketing, Influencer Credibility, and Social Media Interactivity on Brand Loyalty among Generation Z consumers in Indonesia. The research is motivated by the shifting behavior of Gen Z, who are highly influenced by digital content and social media dynamics in forming brand preferences and loyalty. A quantitative explanatory approach was adopted using a survey method. Data were collected from 190 respondents aged 18–26 years who actively use social media and have interacted with brand or influencer content. The sampling technique used was purposive sampling. Data were analyzed using multiple linear regression supported by classical assumption tests. The results reveal that all three variables positively and significantly influence brand loyalty. Among them, Influencer Credibility has the strongest impact, followed by Social Media Interactivity and Digital Content Marketing. The R² value of 0.533 indicates that 53.3 percent of the variation in brand loyalty is explained by the model. The F-test and t-tests confirm the significance of the model, with no issues of multicollinearity or autocorrelation found. These findings highlight the importance for brands to create credible influencer collaborations, engaging content, and active interactions with Gen Z audiences. Future research is recommended to explore mediating variables such as brand trust, digital experience, or emotional engagement.